2011
DOI: 10.1002/mds.23912
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia atrophy in prodromal Huntington's disease is detectable over one year using automated segmentation

Abstract: Background Future clinical trials of neuroprotection in prodromal Huntington’s (known as preHD) require sensitive in vivo imaging biomarkers to track disease progression over the shortest period. Since basal ganglia atrophy is the most prominent structural characteristic of Huntington’s pathology, systematic assessment of longitudinal subcortical atrophy holds great potential for future biomarker development. Methods We studied 36 preHD and 22 age-matched controls using a novel method to quantify regional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 41 publications
(70 reference statements)
2
39
0
Order By: Relevance
“…Based on imaging and neuropathological studies, Majid et al [7] concluded that changes in the globus pallidus are likely to be due to the loss of striatopallidal fibers projecting from striatal medium spiny neurons, such that both striatal and pallidal atrophy in pre-HD may result from the same pathological process of medium spiny neuron loss (and are unlikely due to cell loss within the pallidum). The observed correlations between both cognitive and motor measures and globus pallidus volume, as well as striatal volume, would be consistent with this view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on imaging and neuropathological studies, Majid et al [7] concluded that changes in the globus pallidus are likely to be due to the loss of striatopallidal fibers projecting from striatal medium spiny neurons, such that both striatal and pallidal atrophy in pre-HD may result from the same pathological process of medium spiny neuron loss (and are unlikely due to cell loss within the pallidum). The observed correlations between both cognitive and motor measures and globus pallidus volume, as well as striatal volume, would be consistent with this view.…”
Section: Discussionmentioning
confidence: 99%
“…Significant longitudinal change has also been documented in caudate, putamen, thalamus, and total white matter for pre-HD individuals who are within 15 years of estimated onset [15]. Other regions included in this analysis (nucleus accumbens, hippocampus, and globus pallidus) have been found to be reduced in some studies of pre-HD [3, 6, 7, 10, 46, 47] and correlate with motor scores in pre-HD and HD [3]. …”
Section: Methodsmentioning
confidence: 96%
“…The caudate nucleus is initially more affected than the putamen, the nucleus accumbens appears relatively preserved (Vonsattel et al, 1985;Kassubek et al, 2005). However, when compared with control brains, the nucleus accumbens shows significant volume shrinkage already at preHD stages as detected by magnetic resonance imaging (MRI) and voxel based morphometry (van den Bogaard et al, 2011a;2011b;Majid et al, 2011). These methods can be applied in large cohorts of HD-affected patients in presymptomatic and early stages as well as follow-up studies and are therefore valuable tools for detecting changes of and in specific brain areas.…”
Section: Huntington Diseasementioning
confidence: 99%
“…Clinically, HD is characterized by a triad of motor, cognitive and psychiatric impairments. The morphological correlates of psychiatric-associated symptoms are poorly defined in HD, but there is increasing evidence that the ventral striatum (Enzi et al, 2012;Majid et al, 2011) and the amygdala (Klöppel et al, 2010) are involved in the psychiatric affection of the disease. In this chapter, we introduce the structural components of the VSP and the EA and present the main characteristics of the disorder, with a focus on emotional affection.…”
Section: Introductionmentioning
confidence: 99%
“…Macrostructural changes indicate atrophy of the striatum, cortical tissue and underlying white matter, which have been well quantified by a number of cross-sectional T 1 -weighted volumetric magnetic resonance imaging (MRI) studies during both the premanifest (pre-HD) and symptomatic (symp-HD) stages [9-16]. In addition, a number of longitudinal imaging studies (including those from PREDICT-HD and TRACK-HD) have reported robust increased rates of localized and widespread grey and white matter, cortical and subcortical atrophy in both pre-HD and symp-HD over periods as short as one year [9,10,13,16-22].…”
Section: Introductionmentioning
confidence: 99%